2017
DOI: 10.5505/ias.2017.37888
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Clinical Study of Unani Formulation (Maghz Tukhm-e-Jamun wa Tukhm-e-Hayat) and Metformin in the Management of Ziabetus Shakari (Type 2 Diabetes Mellitus)

Abstract: Diabetes mellitus is a metabolic disorder of multiple etiology, characterized by chronic hyperglycemia with disturbances of carbohydrate, fat, and protein metabolism resulting from defects in insulin secretion, insulin action, or both (1). The cost of diabetes care is high and escalating worldwide. The number of people with diabetes is increasing in every country. Half of the people with diabetes are not aware that they have it, and four out of five people with diabetes live in low-and middleincome countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Diabetes mellitus (Ziabetes shakari) is a metabolic disorder of multiple diagnoses, specified by chronic hyperglycemia with disturbances of carbohydrate, fat, and protein metabolism as a result from defects in insulin secretion, insulin action, or both [1] . In 2000, India (31.7 million) superimposed the world with the highest number of people with diabetes mellitus followed by China (20.8 million) with the United States (17.7 million) in second and third place respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (Ziabetes shakari) is a metabolic disorder of multiple diagnoses, specified by chronic hyperglycemia with disturbances of carbohydrate, fat, and protein metabolism as a result from defects in insulin secretion, insulin action, or both [1] . In 2000, India (31.7 million) superimposed the world with the highest number of people with diabetes mellitus followed by China (20.8 million) with the United States (17.7 million) in second and third place respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of Withania Coagulans extract on reducing glucose levels were similar to the reesults produced by using biguanides and sulphonylureas. 13 Moreover different studies in animal model have also shown that aqueous extract of Withania Coagulans (aqWC) significantly improves pancreatic islets cells architecture. 14 However Anti-diabetic effect of aqueous extract of Withania Coagulans on incretin hormone has not…”
mentioning
confidence: 99%